Allelic variation at the vernalization and photoperiod sensitivity loci in Chinese winter wheat cultivars (Triticum aestivum L.) - Zhang, Xiangfen; Gao, Manxia; Wang, Shasha; Chen, Feng; Cui, Dangqun (Frontiers in Plant Science, 2015)
A total of 205 wheat cultivars from the Yellow and Huai valley of China were used to identify allelic variations of vernalization and photoperiod response genes, as well as the copy number variations (CNVs) of Ppd-B1 and Vrn-A1 genes. A novel Vrn-D1 allele with 174-bp insertion in the promoter region of the recessive allele vrn-D1 was discovered in three Chinese wheat cultivars and designated as Vrn-D1c. Quantitative real-time polymerase chain reaction showed that cultivars with the Vrn-D1c allele exhibited significantly higher expression of the Vrn-D1 gene than that in cultivars with the recessive allele vrn-D1, indicating that the 174-bp insertion of Vrn-D1c contributed to the increase in Vrn-D1 gene expression and caused early heading and flowering. The five new cis-elements (Box II-like, 3-AF1 binding site, TC-rich repeats, Box-W1 and CAT-box) in the 174-bp insertion possibly promoted the basal activity level of Vrn-D1 gene. Two new polymorphism combinations of photoperiod genes were identified and designated as Ppd-D1_Hapl-IX and Ppd-D1_Hapl-X. Association of the CNV of Ppd-B1 gene with the heading and flowering days showed that the cultivars with Ppd-B1_Hapl-VI demonstrated the earliest heading and flowering times, and those with Ppd-B1_Hapl-IV presented the latest heading and flowering times in three cropping seasons. Distribution of the vernalization and photoperiod response genes indicated that all recessive alleles at the four vernalization response loci, Ppd-B1_Hapl-I at Ppd-B1 locus, and Ppd-D1_Hapl-I at the Ppd-D1 locus were predominant in Chinese winter wheat cultivars. This study can provide useful information for wheat breeding programs to screen wheat cultivars with relatively superior adaptability and maturity.